Tackling agricultural water pollution - a 21st-century challenge - Mateo-Sagasta, Javier (2020)
Agriculture is critical to the economies of developing countries. It is the basic source of food supply and a major contributor to economic development. But there is a cost. Today, agricultural water pollution undermines economic growth and threatens the environmental and physical health of millions of people around the world. The annual social and economic costs of agricultural water pollution could reach trillions of dollars. Yet the issue receives scant attention in global research and debate.